2008
DOI: 10.1111/j.1742-6723.2008.01116.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid risk stratification in suspected acute coronary syndrome using serial multiple cardiac biomarkers: A pilot study

Abstract: Serial myoglobin, CK-MB and cTnI have the potential to identify patients who are suitable for early discharge and outpatient work-up. A large multicentre study is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The majority of patients presenting to the ED with chest pain are subsequently found to not have a serious cause and are suitable for further outpatient investigation. 19 Clinicians are required to recognize high-risk patients who need aggressive therapy and to differentiate these from the majority who are suitable for discharge without unnecessary exposure to potentially harmful investigations. In an era of significant ED overcrowding early assessment of risk is necessary to enable timely disposition decisions.…”
Section: Application In Practicementioning
confidence: 99%
“…The majority of patients presenting to the ED with chest pain are subsequently found to not have a serious cause and are suitable for further outpatient investigation. 19 Clinicians are required to recognize high-risk patients who need aggressive therapy and to differentiate these from the majority who are suitable for discharge without unnecessary exposure to potentially harmful investigations. In an era of significant ED overcrowding early assessment of risk is necessary to enable timely disposition decisions.…”
Section: Application In Practicementioning
confidence: 99%
“…Multiple markers analysed on presentation and/ or repeated within a shorter time interval to comply with Emergency Department guidelines, may be sufficient for appropriate risk stratification [8]. Studies have shown sensitivities for AMI of 80-100% for CKMB/ myoglobin up to 4 h post-presentation , 94-96.7% for cTnI/ myoglobin up to 1.5 h post-presentation [89], 92.6% for cTnI/ CKMB up to 8 h post-presentation [90] and 100% for cTnI/ Volume 3 • Issue 11 • 1000222 J Clin Exp Cardiolog ISSN:2155-9880 JCEC, an open access journal CKMB/ myoglobin up to 2 h post-presentation [91] compared with sensitivities for cTn alone of 86 92.3% .These studies used the original WHO criteria/CKMB as the gold standard for the diagnosis of AMI which may over-estimate test performance. However, the emerging generation of hs-Tn assays may obviate the need for these other assays, particularly myoglobin and CK-MB, as elevations may precede clearcut myocardial necrosis.…”
Section: Multi-marker Testingmentioning
confidence: 99%
“…In this issue of the Journal, Macdonald and Nagree present a study that seeks to circumvent these problems by using an earlier and extended panel of biomarkers to identify patients at low risk of ACS. 4 This approach is not novel, but well-conducted studies of this type, which include medium-term census of adverse outcomes, remain a welcome addition to the literature. Inclusion of myoglobin to the biomarker panel measured only 2 h following admission identified all patients who were subsequently found to have elevated troponin levels at 12 h. One patient, who was negative for both myoglobin at 2 h and troponin at 12 h, returned with a fatal ACS within 24 h.…”
Section: Patients Attending the Emergency Department (Ed)mentioning
confidence: 99%
“…In this issue of the Journal, Macdonald and Nagree present a study that seeks to circumvent these problems by using an earlier and extended panel of biomarkers to identify patients at low risk of ACS 4 . This approach is not novel, but well‐conducted studies of this type, which include medium‐term census of adverse outcomes, remain a welcome addition to the literature.…”
mentioning
confidence: 99%